Effects of antipsychotics on intravenous sedation with midazolam and propofol during dental treatment for patients with intellectual disabilities. Issue 4 (17th January 2022) - Oda, Y.; Yoshida, K.; Kawano, R.; Yoshinaka, T.; Oda, A.; Takahashi, T.; Oue, K.; Mukai, A.; Irifune, M.; Okada, Y.
Abstract: Background: Some patients with intellectual disabilities (ID) are prescribed antipsychotic drugs for symptomatic treatment of behavioural disorders. Nevertheless, it can still prove difficult to perform dental treatments safely for some patients with ID. In such cases, treatment under intravenous sedation (IVS) is one option. Sedative, hypnotic and α‐blocking effects of antipsychotic drugs may cause adverse events, such as severe hypotension, among patients who take antipsychotic drugs regularly. This study aimed to investigate the effects of oral antipsychotic medication on cardiovascular function during IVS. Accordingly, we compared mean blood pressure (MBP) and heart rate (HR) between patients who regularly take antipsychotic drugs and patients who do not. Methods: Thirty‐seven patients with ID were enrolled in this study. All participants were outpatients of Special Care Dentistry of general hospital and received dental treatment under IVS performed with a combination of midazolam and propofol. Eighteen patients regularly took antipsychotics (medication group), and 19 patients were not currently taking antipsychotics (non‐medication group). MBP, HR, dose, and effect‐site concentration of intravenous sedative medications were measured at three points: 'before IVS', 'at optimal sedation', and 'during dental treatment'. Results: The magnitude of reduction of MBP was significantly smaller in the medication group than in the non‐medication group ( P < 0.023). However, there were no differences in MBP, HR, dose, and effect‐site concentration of midazolam and propofol between groups at any point. Conclusion: These results suggest that antipsychotic medication may not have clinically significant adverse effects on cardiovascular fluctuations during dental treatment under IVS for persons with ID.